INTER/MULTICULTURAL EDUCATION: HOW CAN IT CONTRIBUTE TO A MORE EFFECTIVE CLASSROOM PRACTICE? - Radeck, Ereni (Revista Gênero e Interdisciplinaridade, 2024)
Introduction: Reflection on the possibilities and intercultural challenges encountered in the pedagogical work of integrating teachers, specifically in the assistance provided to high school students, leads us to studies that seek to identify interfering factors or pedagogically outdated models being followed. This article presents a contribution to the study of intercultural teacher education, aiming to enhance knowledge through a literature review on the relevance of cultural conceptions. Furthermore, it seeks to innovate and propose new pedagogical models to address the challenges of interculturality, both in the behavior and professional practice of integrating teachers. Objective: To address the intercultural challenges present in the context of inclusive education, especially in the assistance provided to students with disabilities. This text is based on research by authors who contribute to theoretical understanding, assisting in applied classroom practice. The research primarily aims to answer the question: How does intercultural education contribute to pedagogical practice, considering public policies? Results: Through studies, projects, reflections, and research, it is evident that the debate on intercultural education is gaining prominence in Latin American societies. In this scenario, it is essential to promote interventions to ensure that government and academic community policy initiatives, in proposing degree courses, foster critical intercultural education capable of intervening in societal transformation and construction. Conclusion: Therefore, there is a need for pedagogical resources, teacher training to better serve students and connect with learning, as well as proper assessment of children.